Design and Synthesis of Pathway Genes for Polyketide Biosynthesis - Peirú, Salvador (2009)
In this chapter we describe novel methods for the design and assembly of synthetic pathways for the synthesis of polyketides and tailoring sugars. First, a generic design for type I polyketide synthase genes is presented that allows their facile assembly for the expression of chimeric enzymes in an engineered Escherichia coli host. The sequences of the synthetic genes are based on naturally occurring polyketide synthase genes but they are redesigned by custom-made software to optimize codon usage to maximize expression in E. coli and to provide a standard set of restriction sites to allow combinatorial assembly into unnatural enzymes. The methodology has been validated by building a large number of bimodular mini-PKSs that make easily assayed triketide products. Learning from the successful bimodules, a conceptual advance was made by assembling genes encoding functional trimodular enzymes, capable of making tetraketide products. Second, methods for the rapid assembly and exchange of sugar pathway genes into functional operons are described. The approach was validated by the assembly of the 15 genes for the synthesis of mycarose and desosamine in two operons, which yielded erythromycin C when coexpressed with the corresponding PKS genes. These methods are important enabling steps toward the goals of making designer drugs by polyketide synthase and sugar pathway engineering and, in the shorter term, producing by fermentation advanced intermediates for the synthesis of compounds that otherwise require large numbers of chemical steps.